EFL Students’ Perceptions of TPACK Implementation in a Hybrid Classroom - Radiah Zakiyati Alim; Nur Alim (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
Although a growing body of research examines Hybrid Learning, little attention has been paid to analyzing the students’ perceptions toward implementing the TPACK framework as an instructional reference in hybrid EFL classroom settings. To fill this void, this research intended to explore the EFL students’ perceptions regarding implementing TPACK in hybrid EFL classrooms in the context of a private Islamic senior high school. The study used a quantitative approach adopting a survey method with an online distributed form. Data were collected through a survey questionnaire, and semi-structured open-ended questions were descriptively analyzed and thematically coded. The TPACK survey revealed 77.8% of the respondents agreed that the EFL teacher had successfully integrated technology into practice. However, with 54.58% valid responses in the open-ended data, the EFL teacher implemented technological adaptation to facilitate classroom meetings by alternating to virtual modes but failed to explore and recognize the individual EFL learning needs of the students. The study concluded that the respondents’ perception toward implementing TPACK in hybrid learning was positive in that it granted easy access to classroom documents and resources, supported multiple modes of material delivery, valued connectivity and interactivity, and provided flexible scheduling. This study addressed some issues regarding the advantages and disadvantages of a technology-equipped classroom in a hybrid context. The issues foretell the EFL teachers never to limit their attention to physical preparations and necessities.